2005
DOI: 10.1080/00365540510036606
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in patients with haemorrhagic fever with renal syndrome

Abstract: The purpose of the study was to assess the incidence, type and dynamics of electrocardiography (ECG) alterations in patients with haemorrhagic fever with renal syndrome (HFRS) according to different stages of the disease. 79 patients hospitalized at the University Hospital for Infectious Diseases in Zagreb during the large HFRS outbreak in Croatia in 2002 were retrospectively analysed. HFRS diagnosis was confirmed by enzyme-linked immunosorbent assay. A 12-lead resting ECG was obtained. 30 (38%) patients had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
3
15
0
1
Order By: Relevance
“…Previously, respiratory symptoms were commonly attributed to fluid overload as a result of renal failure. However, increasing evidence show that lung and heart involvement is common during the acute phase of HFRS [10, 11, 22, 23]. Concerning the cases of European hantavirus infection in our present report, there was only mild or no renal impairment at the time of admission, whereas the respiratory involvement was early and severe, consistent with acute respiratory distress syndrome (ARDS), fulfilling criteria of HPS according to CDC case definition [19].…”
Section: Discussionsupporting
confidence: 47%
“…Previously, respiratory symptoms were commonly attributed to fluid overload as a result of renal failure. However, increasing evidence show that lung and heart involvement is common during the acute phase of HFRS [10, 11, 22, 23]. Concerning the cases of European hantavirus infection in our present report, there was only mild or no renal impairment at the time of admission, whereas the respiratory involvement was early and severe, consistent with acute respiratory distress syndrome (ARDS), fulfilling criteria of HPS according to CDC case definition [19].…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, >25% of HFRS patients in Sweden had evidence of disseminated intravascular coagulation, which correlated with HFRS disease severity (14). Taken together, data from these studies (6,1015) and the present data indicate a possible association between PUUV infection and precipitation of CVD events that could eventually lead to death.…”
Section: Discussionsupporting
confidence: 77%
“…The elevated risk is more pronounced during the acute phase of respiratory viral infection but can still be increased 3 months afterwards (9). Abnormal electrocardiograms (10,11) and myocarditis (12) have been observed during the acute phase of PUUV infection, indicating an association between PUUV infection and cardiovascular disorders. Furthermore, PUUV antigen has been found in cardiac tissue (6), and other studies have documented the essential role of coagulopathy in HFRS disease severity (1315).…”
Section: Discussionmentioning
confidence: 99%
“…These findings resolved spontaneously as the patients recovered, consistent with a previous report. 19 Puljiz and others reported that all ECG alterations were transient and all patients, including three with myocarditis, recovered spontaneously. However, in our case series, two of four patients with cardiac manifestations, one with myocarditis and one with pericarditis, died during the oliguric phase.…”
mentioning
confidence: 99%